AN EXPOSITION OF THE SOCIO-ECONOMIC IMPACTS OF CONSTRUCTION SITE ACCIDENTS IN NIGERIA - VN, Okorie; CC, Adindu (Journal of Surveying, Construction and Property, 2020)
Nigeria’s construction sector is a key to the development of national economy, especially its contribution to employment creation and value addition to the national gross domestic product. The mode of workforce recruitment, job retention and disengagement are largely informal with an attendant high rate of construction site accidents often resulting in injuries and fatalities to persons and properties. This study examines the social and economic effects of site accidents on Nigerian economy. Descriptive survey research was employed with structured questionnaire as research design and administered to twenty major construction companies operating within southern Nigeria. Interviews were also conducted with owners/directors, contract managers, construction project managers, health and safety officers, site managers, affected workers and families alike to validate study results. Data obtained from field survey were analyzed. The study revealed loss of company productivity, reduction in living standards as having the most economic impacts on construction companies and their affected workers/families respectively. Additionally, loss of customers’ confidence and loss of the family bread winner represents the highest social impacts on the construction companies and affected workers/ families. The study concludes that there is existence of low commitment towards workers’ health, safety and general wellbeing by Nigerian construction firms. The study therefore, recommends that government at all levels should enact and strictly enforce Construction Industry Health and Safety Laws, and sanction firms that contravene Health and Safety Regulations. Furthermore, construction firms irrespective of size should demonstrate visible leadership towards workers’ health and safety.